Association between intimate partner violence during pregnancy and risk of preterm birth - Sanni Yaya; Emmanuel Kolawole Odusina; Nicholas Kofi Adjei; Olalekan A. Uthman (BMC, 2021)
Abstract Background Preterm birth is a risk factor for child survival in both the short and long term. In Zimbabwe, the prevalence of preterm birth is rising, and there are growing concerns about the adverse consequences. This study explored the association between intimate partner violence (IPV) during pregnancy and preterm birth in Zimbabwe. Methods Using data from the 2015 Zimbabwe Demographic and Health Survey, we applied propensity score matching to estimate the effect of IPV during pregnancy on preterm birth among women of reproductive age (15-49 years). A total of 4833 pregnant women who gave birth during the five years preceding the survey were analysed. Results We successfully matched 79 women who were exposed to IPV during pregnancy to 372 unexposed during pregnancy. Using the matched sample, the probability of preterm delivery was significantly higher among women who were exposed to IPV during pregnancy than those who were not exposed. The findings showed that 7 out of 79 (8.9%) of women exposed to IPV during pregnancy experienced preterm delivery, and 11 out of 372 (3.0%) of those who were not exposed to IPV during pregnancy experienced preterm delivery. In the urban areas, those exposed to IPV during pregnancy were almost five times more likely to experience preterm delivery (OR = 4.8, 95% CI 2.0-11.6), but the association was not significantly different among women in rural areas. Conclusion The findings showed that women exposed to IPV during pregnancy were at increased risk of preterm birth. Some of the risk factors associated with IPV were urban residence, low economic status and unemployment. Effective policies and programmes are required to address the issue of IPV in Zimbabwe.